2020
DOI: 10.1177/0090591720927800
|View full text |Cite
|
Sign up to set email alerts
|

“The State was Patiently Waiting for Me to Die”: Life without the Possibility of Parole as Punishment

Abstract: Despite its growing use over past decades, there has been relatively little public or scholarly discussion of life sentences that deny the possibility of parole. This essay outlines the labyrinthine legal and political developments that have rendered life imprisonment difficult to address—including the intertwined histories of the death penalty and civil death—and draws upon the life writing of those serving life to theorize a more distinct understanding of this punishment. Witnesses reveal how the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…Where Berkman located the modern prison's emergence in the religious, legal, and economic conditions of the United States, political scientists have traced the increase in contemporary sentencing and severity to intersections of race and law (Alexander 2012;Beckett and Francis 2020;Murakawa 2014), the punitiveness of public opinion and culture (Barkow 2019;Enns 2016, 5;Howard 2017), and the "grand social experiment" of penal policy from the mid-twentiethcentury onward (Clear and Frost 2014, 48). Where Berkman ("Crime & Prisons" n.d.,3) urged Americans to "take a personal interest" in prisons' political implications, scholars have studied incarceration's impact on participation levels (Walker 2020; Weaver and Lerman 2010), "conceptions of citizenship" (Gottschalk 2015, 2), or democratic theory (Bennett 2021;Benson 2019;Dilts 2014). Where Berkman (1999, 215, 301-7) witnessed prisoners on strike and working toward reform, political scientists have examined democratic action behind bars (Berk 2018;Gortler 2022) or what David Skarbek (2020) calls the "extralegal governance institutions" whereby imprisoned people maintain order.…”
Section: "Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Where Berkman located the modern prison's emergence in the religious, legal, and economic conditions of the United States, political scientists have traced the increase in contemporary sentencing and severity to intersections of race and law (Alexander 2012;Beckett and Francis 2020;Murakawa 2014), the punitiveness of public opinion and culture (Barkow 2019;Enns 2016, 5;Howard 2017), and the "grand social experiment" of penal policy from the mid-twentiethcentury onward (Clear and Frost 2014, 48). Where Berkman ("Crime & Prisons" n.d.,3) urged Americans to "take a personal interest" in prisons' political implications, scholars have studied incarceration's impact on participation levels (Walker 2020; Weaver and Lerman 2010), "conceptions of citizenship" (Gottschalk 2015, 2), or democratic theory (Bennett 2021;Benson 2019;Dilts 2014). Where Berkman (1999, 215, 301-7) witnessed prisoners on strike and working toward reform, political scientists have examined democratic action behind bars (Berk 2018;Gortler 2022) or what David Skarbek (2020) calls the "extralegal governance institutions" whereby imprisoned people maintain order.…”
Section: "Wmentioning
confidence: 99%
“…On sentencing policy, Marie Gottschalk (2015, 165-6) has identified how legislative efforts to lessen the incarceration of "nonviolent, nonserious, and nonsexual offenders… has contributed to the further demonization of people convicted of sex offenses or violent crimes." On capital punishment, former prosecutors (Capers 2012) and scholars (Bennett 2021;Seeds 2022) have shown that movements to abolish the death penalty catalyzed the rise in life imprisonment since the 1970s: recent court cases limiting juvenile life sentences have in turn reinforced that adults deserve "death by prison." On defunding prisons and police, Maya Schenwar and Victoria Law (2020, 5-8) have criticized federal laws like the First Step Act that reinvested prison money in other forms of surveillance, whereas Alex Vitale (2017) and Geo Maher (2022) argue that recent attempts to reform law enforcement have insufficiently interrogated policing's role in society.…”
Section: Conclusion: the Unresolved Tensions Of American Prison Politicsmentioning
confidence: 99%